Assessment of the Level of Innovativeness of Enterprises in Poland in the Era of Industry 4.0 - Dariusz WIELGÓRKA (Communications of International Proceedings, 2021)
Innovation has a significant impact on socio-economic development. They are a factor and an opportunity for the development of enterprises, allowing them to gain a competitive advantage on the market. To achieve a good position and success on the market, these enterprises should create and implement innovations.  In order to achieve this, it is necessary to manage them properly and skilfully. In order to effectively implement innovations in an enterprise it is necessary to know their level, identify implementation barriers. The main objective of the research is to evaluate the level of innovativeness of Polish enterprises in comparison to enterprises from other selected EU countries using statistical methods. If companies have the opportunity to implement innovations, it will affect their development and active participation in the fourth industrial revolution - the concept of Industry 4.0. Innovations should also bring concrete financial benefits for the company, which will allow for its further development, achieving market success, manifested in sales growth and profit. The concept of innovation has evolved over the years, but its essence has remained unchanged. An innovation is a novelty, the first application of which may be new both for the enterprise itself and on a global economic scale.
Keywords: Innovation; Industry 4.0; types of innovation; barriers to innovation